2017
DOI: 10.1177/2374373517699273
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perceptions of Clinician’s Empathy

Abstract: The prominence of reciprocal understanding in patient–doctor empathic engagement implies that patient perception of clinician’s empathy has an important role in the assessment of the patient–clinician relationship. In response to a need for an assessment tool to measure patient’s views of clinician empathy, we developed a brief (5-item) instrument, the Jefferson Scale of Patient Perceptions of Physician Empathy (JSPPPE). This review article reports evidence in support of the validity and reliability of the JSP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 28 publications
2
50
0
6
Order By: Relevance
“…These could be explained by differences in the content of the discussion between the resident and patient or perhaps by an unconscious bias of which the resident was unaware. The differences noted in the facial expressions of residents by gender might represent a mirroring of the patients' expressions by the female residents, a manifestation of empathy, 25 and could help explain the increased likelihood of patient satisfaction with the encounter when the clinician was female.…”
Section: Discussionmentioning
confidence: 99%
“…These could be explained by differences in the content of the discussion between the resident and patient or perhaps by an unconscious bias of which the resident was unaware. The differences noted in the facial expressions of residents by gender might represent a mirroring of the patients' expressions by the female residents, a manifestation of empathy, 25 and could help explain the increased likelihood of patient satisfaction with the encounter when the clinician was female.…”
Section: Discussionmentioning
confidence: 99%
“…e scale score is generated by adding individual item scores; a higher score is correlated with a more empathic perception of the physician by the patient. Psychometrics of the original [40], a French [50], and a modified Spanish version [51] of the JSPPPE have been studied; evidence of validity and reliability for all versions has been documented. (7) e Visual Analog Scale (VAS) for pain, a unidimensional single-item scale assessing the patients' level of pain, consisting of a straight line with the endpoints denoting two extremes, i.e., "no pain" and "pain as bad as it could be" [52].…”
Section: Group Amentioning
confidence: 99%
“…Among 14 first-person assessments, only 6 of them had evidence of either reliability or internal consistency testing, whereas among 5-second person assessments, only the Consultation And Relational Empathy (CARE) scale demonstrated such evidence. Lately, evidence of validity and reliability for the Jefferson Scale of Patient Perception of Physician Empathy (JSPPPE), the shortest available instrument (5 items), was published [40].…”
Section: Introductionmentioning
confidence: 99%
“…In the practice of health and medicine, the practitioner's empathic skill can help to build patient trust, lower patient distress and anxiety level as well as improve patient satisfaction . As an integral part of the health care team, dietitians play an important role in providing nutrition‐focused preventive services in both clinical and community settings.…”
Section: Introductionmentioning
confidence: 99%
“…2 Rogers (1969), the founder of humanistic approach concluded that the important elements of empathy in a health-care context are understanding the client's feeling, reflecting the client's mood and content of conversation and sharing the client's feeling. 3 In the practice of health and medicine, the practitioner's empathic skill can help to build patient trust, 4 lower patient distress and anxiety level 4 as well as improve patient satisfaction. 5,6 As an integral part of the health care team, dietitians play an important role in providing nutrition-focused preventive services in both clinical and community settings.…”
Section: Introductionmentioning
confidence: 99%